Isolation of a novel psychrotrophic fungus for efficient low-temperature composting. (July 2021) - Jiang, Gaofei; Chen, Peijie; Bao, Yanzhuo; Wang, Xiaofang; Yang, Tianjie; Mei, Xinlan; Banerjee, Samiran; Wei, Zhong; Xu, Yangchun; Shen, Qirong
Highlights: A novel psychrophilic fungus Aureobasidium was screened and used in low temperature composting. This psychrophilic fungus accelerated temperature rises at early stage of composting. This psychrophilic fungus increased the compost maturity and improved compost quality. Abstract: This study aimed to isolate psychrotrophic cellulose-degrading fungi and to investigate their application potential for composting in cold climate regions in China. One out of five psychrotrophic cellulose-degrading fungal isolates was identified as a novel fungal species, Aureobasidium paleasum sp. nov., with a strong straw degradation potential. Enzyme activity assays and FITR spectroscopy revealed high cellulolytic activities of this psychrotrophic fungus at lower temperatures, with high thermal adaptability from 5 °C to 50 °C (optimum at 10 °C). A. paleasum efficiently decomposed rice straws and cellulose at 10 °C compared to the common cellulose-degrading fungus Penicillium oxalicum . In comparison to P. oxalicum, A. paleasum shortened the thermophilic stage, enhanced compost maturity and improved compost quality. Our work suggests that the psychrotrophic fungus A. paleasum is efficient for rice straw degradation and composting at low temperatures, highlighting its application potential for composting in colder regions.